Corrigendum - Jalil MA (Dove Medical Press, 2012)
Jalil MA, Moongfangklang N, Innate K, Mitatha S, Ali J, Yupapin PP. Molecular network topology and reliability for multipurpose diagnosis. Int J Nanomedicine. 2011;6:2385–2392.The author order and affiliations were incorrect in the published version. The correct author order and affiliations are as follows:N Moongfangklang1MA Jalil2K Innate3S Mitatha1J Ali4PP Yupapin31Hybrid Computing Research Laboratory, Faculty of Engineering, King Mongkut’s Institute of Technology Ladkrabang, Bangkok, Thailand; 2Ibnu Sina Institute of Fundamental Science Studies, Nanotechnology Research Alliance, University of Technology Malaysia, Johor Bahru, Malaysia; 3Nanoscale Science and Engineering Research Alliance, Advanced Research Center for Photonics, Faculty of Science, King Mongkut’s Institute of Technology Ladkrabang, Bangkok, Thailand; 4Institute of Advanced Photonics Science, Nanotechnology Research Alliance, University of Technology Malaysia, Johor Bahru, MalaysiaRead the original article.